Post Processing Analysis of Dynamic Calculation Results of a Special Vehicle Based on SIMPACK Model - Jianjun ZOU; Zhihui HUANG (机车电传动)
4 kinds of filtering methods commonly used in SIMPACK post processing were discussed. Taking the dynamic indexes calculation under curves condition as an example, the calculated results obtained by the 4 filtering methods were compared with those of the waveforms that were not processed by using the 4 filtering methods, and the filtering was more intuitively matched with the actual results. From the comparison, the result of using the 9 thousand and 975 quantile was more reliable. The research could be used for post processing analysis of dynamic calculation results by using SIMPACK software in the future, and provide reference for the selection of filtering methods.